Hatching-Box: Automated in situ monitoring of Drosophila melanogaster development in standard rearing vials - Julian Bigge; Maite Ogueta; Luis Garcia; Benjamin Risse (PLoS ONE, 2025)
In this paper we propose the Hatching-Box, a novel in situ imaging and analysis system to automatically monitor and quantify the developmental behavior of Drosophila melanogaster in standard rearing vials and during regular rearing routines, reducing the need for explicit experiments.This is achieved by combining custom tailored imaging hardware with dedicated detection and tracking algorithms, enabling the quantification of larvae, filled/empty pupae and flies over multiple days. Given the affordable and reproducible design of the Hatching-Box in combination with our generic client/server-based software, the system can easily be scaled to monitor an arbitrary amount of rearing vials simultaneously. We evaluated our system on a curated image dataset comprising nearly 416,000 annotated objects and performed several studies on real world experiments. We successfully reproduced results from well-established circadian experiments by comparing the eclosion periods of wild type flies to the clock mutants pershort, perlong and per0 without involvement of any manual labor. Furthermore we show, that the Hatching-Box is able to extract additional information about group behavior as well as population development and activity. These results not only demonstrate the applicability of our system for long-term experiments but also indicate its benefits for automated monitoring in the general cultivation process.